Oral supplementation with Lactobacillus fermentum MC018 improves intestinal health, immune response, and growth performance of Zi geese infected with Escherichia coli XH197291 - Li, Yang; Liu, Meng; Li, Zehao; Dong, Meiqi; He, Linru; Li, Peilong; Chen, Ruosi; Liang, Yue; Yang, Lijia; Li, Fei; Zhou, Yulong; Zhu, Zhanbo; et al. (Frontiers in Veterinary Science, 2025)
IntroductionEscherichia coli infection causes severe diarrhea, decreases growth performance, and increases mortality of poultry, which imposes a significant economic burden on the poultry industry and severely limits its growth.MethodsHere, to investigate the effects of Lactobacillus on the intestinal health, immune response, and growth performance of E. coli-infected goslings, we established a geese model infected with an Stx2f gene-carrying E. coli strain and analyzed the probiotic characteristics of three Lactobacillus isolates obtained from the cecum of healthy geese. In an in vivo study, Zi geese were administered daily gavage of L. johnsonii MC006, L. salivarius MC013, or L. fermentum MC018 (109 CFU/mL) from 1 d of age for 21 d, followed by treatment with E. coli XH197291 gavage (109 CFU/mL) on day 8.ResultsThe results showed that E. coli XH197291-infected geese exhibited depression, intestinal damage, reduced average daily gain, increased feed conversion ratio, and 100% diarrhea incidence within 48 h post-infection. Remarkably, among the three Lactobacillus isolates, L. fermentum MC018 showed the potential to function as a probiotic because of its ability to resist acid and bile degradation, antibacterial effect, and adhesion property. Notably, oral supplementation containing L. fermentum MC018 alleviated diarrhea and intestinal histological lesions, reduced E. coli counts in both ileum and rectum, increased the population of lactic acid bacteria, and improved the growth performance of E. coli-infected geese. Geese treated with L. fermentum MC018 gavage had higher serum diamine oxidase (p < 0.01) and IgM (p < 0.05) levels than those in the model group. L. fermentum MC018 reduced the levels of IL-1β, IL-6, and TNF-α in intestinal tissues following E. coli infection. Compared to L. salivarius MC013, L. fermentum MC018 increased the levels of ZO-1 in the duodenum and Claudin-1 in the ileum.DiscussionThese findings suggest that L. fermentum MC018 is a promising probiotic strain for use as a potential alternative to antibiotics for controlling avian colibacillosis.